The role of digital and climate-smart agriculture in climate change mitigation: A systematic mapping protocol for South Asia and sub-Saharan Africa - Gardezi, Maaz; Xinjing Yu; Carcamo, Pablo; Kumari, Sheetal (CGIAR, 2024)
Climate-smart agriculture is a key global policy priority due to its potential to support climate change adaptation, mitigation, and food security through innovative practices and technologies. Recent advancements in digital agriculture technologies, such as precision agriculture and data analytics, are enabling its implementation. However, little is known about how digital agriculture can support smallholders in achieving overarching mitigation goals without compromising food security and on-farm adaptation outcomes. A lack of understanding of the scope and impact of these technologies hinders policymakers from developing strategies to effectively address their potential risks and benefits. This protocol outlines the methodology employed for conducting a systematic map to compile and synthesize evidence from South Asia and Sub-Saharan Africa on the evolution, drivers, barriers, and on-farm impacts of digital climate-smart agriculture for climate change mitigation. We will use two complementary search strategies: (i) a systematic bibliographic search; and (ii) a citation chase approach. Articles will be included based on pre-defined criteria aligned with the Population, Intervention and Outcome design. The systemic map will identify knowledge gaps and clusters, with results presented through narrative synthesis, an evidence atlas, and other visualization.